Lithopetrographic and geochemical features of the Saalian tills in the Szczerców outcrop (Poland) in various deformation settings - Wachecka-Kotkowska Lucyna (De Gruyter, 2021)
This paper presents the results of new studies of Saalian tills, from the Ławki and Rogowiec formations, filling the Kleszczów Graben. The study area is located in the Szczerców outcrop, Bełchatów Lignite Opencast Mine, central Poland. Laboratory studies included macrofossil analysis of the deposits, as well as petrographic and geochemical (neodymium isotope ratio) measurements. The studies were carried out in 2014–2016 and resulted in both establishing the sedimentary Saalian complex and constructing geological cross-sections and a synthetic lithostratigraphic profile. Development of sediments in this part of the Kleszczów Graben in the Pleistocene was largely influenced by tectonic factors (Chabielice fault, Dębina Salt Dome) and glacitectonic processes (Wartanian Glaciation). The Saalian tills (T4 – Ławki and T7 – Rogowiec lithotypes) are between the Holsteinian sand with macroremnants of trees and the Eemian gyttja and peat. Petrographic coefficients for lithotype T4 (Ławki Formation) are 1.33–1.06–1.01 and 0.12 and for lithotype T7 (Rogowiec Formation) are 1.29–1.23–1.04 and 0.12. Investigations of the Nd isotopic compositions of the studied samples reinforce our interpretations of till deformation and tentative lithostratigraphic correlations. Neodymium isotope ratios “P” (−14.4 ± 0.7) and “D” (−12.4 ± 0.3) ε Nd values (2σ) correspond to mean signatures of Saalian glacigenic moraine sediment. This proves that ε Nd values less than −12.4 reflect the southern Fennoscandian Ice Sheet sediment provenance, but ε Nd values greater than −12.4 indicate the western European origin.